Marine Microplastic Levels and the Prevalence of Cardiometabolic Diseases in US Coastline Counties - Bhargav Makwana; Sumanth Khadke; Ashish Kumar; Khurram Nasir; Rishi Wadhera; Rikin Shah; Sudip Sheth; Yixin Kong; Ana Navas‐Acien; Gary Adamkiewicz; Sanjay Rajagopalan; Sadeer Al‐Kindi; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although micro‐ and nanoplastics are an emerging risk factor for the development of cardiovascular diseases, the association of marine microplastic levels (MMLs) with the burden of cardiometabolic diseases at a population level remains unexplored. We investigated the relationship between the mean microplastic concentration in ocean water within 200 nautical miles of the US coastline and the prevalence of type 2 diabetes, coronary artery disease, and stroke in nearby counties. Methods Microplastic concentration data within 200 nautical miles of the US coastline were geospatially analyzed to calculate mean MMLs. The coastal counties were stratified into 4 categories based on MMLs in the adjacent ocean water body: low, medium, high, or very high. The Behavioral Risk Factor Surveillance System 2019 to 2020 survey data were used to identify the prevalence of type 2 diabetes, coronary artery disease, and stroke in these counties. Univariate and population‐weighted multivariate quasi‐Poisson regression, adjusted for county‐level confounding variables, was used to evaluate the unadjusted and adjusted associations between disease prevalence and MMLs. Results The mean age of the population was 43±6 years. After adjusting for age, sex, physician access, and socioenvironmental vulnerabilities at the county level, counties with very high MMLs exhibited an 18%, 7%, and 9% higher adjusted prevalence of type 2 diabetes, coronary artery disease, and stroke, respectively, compared with those with low levels. Conclusion Marine microplastic levels were significantly associated with the prevalence of cardiometabolic diseases in coastal counties. Comprehensive studies at an individual level are needed to further investigate the health impacts of microplastic pollution.